Edukasi Interaksi Obat Dengan Makanan Pada Pasien Yang Menggunakan Terapi Jangka Panjang - Jabir, M. Agus; Bayaranie, Meidyana; Cahya, Mochamad Robby Fajar; Djunaedi, Djunaedi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Long-term therapy for patients with chronic diseases requires regular and continuous medication use. One common problem in long-term treatment is a lack of patient understanding of drug-food interactions. These interactions can affect drug effectiveness, increase the risk of side effects, and decrease the success of therapy. This Community Service activity aims to increase patient knowledge and awareness regarding drug-food interactions to support the safety and effectiveness of long-term therapy. Implementation methods included health education, drug counseling, interactive discussions, and evaluation through pre- and post-tests. The results of the activity showed a significant increase in patient knowledge regarding the types of drug-food interactions and how to consume them correctly. This education is expected to improve therapy adherence and prevent drug-related problems in patients on long-term therapy.